2015
DOI: 10.1007/jhep03(2015)018
|View full text |Cite
|
Sign up to set email alerts
|

One-loop partition functions in deformed N = 4 $$ \mathcal{N}=4 $$ SYM theory

Abstract: We study the thermodynamic behaviour of the real β-and γ i -deformation of N = 4 Super Yang-Mills theory on R×S 3 in the planar limit. These theories were shown to be the most general asymptotically integrable supersymmetric and non-supersymmetric field-theory deformations of N = 4 Super Yang-Mills theory, respectively. We calculate the first loop correction to their partition functions using an extension of the dilatation-operator and Pólya-counting approach. In particular, we account for the oneloop finite-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 46 publications
0
36
0
2
Order By: Relevance
“…This could provide a connection to the cases of the Hagedorn temperature in the pp-wave or spin-matrix-theory limits [34][35][36][37][38][39][40][41][42][43]. Moreover, it would be interesting to consider the Hagedorn temperature for integrable deformations of N = 4 SYM theory (see [44] for one-loop results) and for the three-dimensional N = 6 superconformal Chern-Simons theory, for which a QSC formulation for the spectral problem exists as well [45]. In particular, it would be intriguing to study what happens at strong coupling in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…This could provide a connection to the cases of the Hagedorn temperature in the pp-wave or spin-matrix-theory limits [34][35][36][37][38][39][40][41][42][43]. Moreover, it would be interesting to consider the Hagedorn temperature for integrable deformations of N = 4 SYM theory (see [44] for one-loop results) and for the three-dimensional N = 6 superconformal Chern-Simons theory, for which a QSC formulation for the spectral problem exists as well [45]. In particular, it would be intriguing to study what happens at strong coupling in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…(B.12) 56 The factor of 2 depends on the convention for the modified effective planar coupling constant (3.19).…”
Section: B2 Sl(2) Subsectormentioning
confidence: 99%
“…An operator variant of this formulation was given in[17,19] and a different integral representation can be found in[56].…”
mentioning
confidence: 99%
“…The partition function and Hagedorn temperature have also been studied in integrable deformations of N ¼ 4 SYM theory up to one-loop order [38], where it was found that although ZðTÞ is different, T H is unchanged. It would be interesting to see whether this statement continues to hold at higher loop orders.…”
mentioning
confidence: 99%